Risk information seeking and processing of beef producers in the Southeast United States - Waggie, Rachel Elaine (Kansas State University, 2020)
The beef industry is ever evolving and plays a vital role in the United States economy. Many factors determine the impact of a beef operation and its contributions to the industry as a whole. Beef cow-calf operations in the Southeast United States are often criticized for being behind-the-times in management practices used and being slower to adopt new technologies. Is there a reason these producers manage differently than those in other regions? What impact, if any, do communication practices have on the management decisions for these operations? The purpose of this study was to better understand how Southeast beef cow-calf producers seek and process risk information about herd management and to determine communication preferences of these producers. The Risk Information Seeking and Processing (RISP) model was used to develop a survey, which was distributed through various beef producer organization channels to 11 Southeast states: Alabama, Florida, Georgia, Kentucky, Louisiana, Mississippi, North Carolina, South Carolina, Tennessee, Virginia, and West Virginia. The specific research objectives were to 1) define demographic and sociocultural characteristics of beef cow-calf producers in the Southeast United States, and 2) determine the perceived knowledge gap of beef cow-calf producers in the Southeast United States as it relates to risk management knowledge. The research question addressed by this study asked how beef cow-calf producers in the Southeast United States use different communication channels to influence their level of knowledge regarding risks facing their operations. Researchers proposed the following hypothesis, based on the RISP model: as the level of perceived risk increases, beef cow-calf producers in the Southeast United States will seek risk information through nonroutine channels. A majority of respondents identified their beef operations as having moderate risk in the areas of animal health, breeding management, calving management, animal growth, economic management, and marketing/selling calves. Perceived risk of weaning was categorized as moderately low. The preferred channel to receive beef-related information was through print magazines, and the preferred source of information was local extension. Additionally, respondents appeared to generally seek heuristic messages about beef risk management. In this study, no information was collected to assess the processing of these messages.
Keywords: RISP; Beef industry; Agricultural communication; Risk information seeking and processing